Synthesis of Dibenzothiophene, Dibenzofuran and Carbazole Donor–Acceptor Chromophores - Jepsen, Tue Heesgaard; Larsen, Mogens; Jørgensen, Morten; Nielsen, Mogens Brøndsted (Synthesis, 2013)
We present efficient synthetic protocols for functionalizing dibenzothiophene, dibenzofuran, and carbazole with hydroxy and nitro or cyano groups. The synthesis of these donor–acceptor chromophores is based on a key Suzuki–Miyaura coupling using an appropriately substituted aromatic boronic acid. Subsequent intramolecular SNAr reaction allows formation of the dibenzothiophene and dibenzofuran scaffolds, while a carbon–hydrogen activation reaction is employed to afford the carbazole. A final demethylation step unmasks the phenol moiety of the tricyclic chromophores. The UV/Vis absorption properties of the phenol and phenolate forms of these chromophores are also studied.
Keywords: dibenzothiophene; dibenzofuran; carbazole; heterocycles; palladium; phenols